Development of the root pole and cell patterning in Arabidopsis roots. - Costa, S; Dolan, L (2000)
The root forms at the basal end of an axis that is set up early in embryogenesis, and recent genetic analysis has indicated that auxin transport is required for the formation of the root pole. Drug studies show that auxin transport is also required for the maintenance of the tissue organisation in the seedling root. These studies support existing models for tissue patterning that involve canalised auxin flow. Molecular insights into the mechanism of cell-type specification and patterning has come from the epidermis where positionally controlled cell specification is regulated by a cascade of transcription factors.